STRATEGI PEMASARAN KREDIT PEMILIKAN RUMAH FLPP PADA PT. BANK SUMUT KCP SYARIAH KISARAN: UNTUK MENINGKATKAN POPULARITAS PRODUK - Sri Anjani; Juliana Nasution; Wahyu Syarvina (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study critically examines the marketing strategies employed by PT. Bank Sumut KCP Syariah Kisaran to enhance the visibility and uptake of its Sharia-based Mortgage Loan (KPR) supported by the Housing Finance Liquidity Facility (FLPP). Using a descriptive qualitative method, data were gathered through interviews, observations, and document analysis, then analyzed thematically. The findings indicate that the bank implements a marketing mix strategy encompassing product, price, place, and promotion. This integrated approach has effectively expanded the customer base and helped meet annual financing targets. Key contributing factors include excellent service delivery and proactive promotional activities such as direct customer engagement, which have strengthened public trust in the Sharia-compliant financing scheme. These results provide practical insights for other Islamic financial institutions seeking to develop marketing strategies for inclusive financing products, particularly those targeting low-income communities.